Development of A Multimedia-Based English Vocabulary Learning Application Through Short Qur'anic Verses Using a Computer Based Instruction Approach - Lahmudin Sipahutar; Nursyah Handayani; Elvin Syahrin (International Journal of Computer and Information System (IJCIS), 2026)
This study aims to develop a multimedia-based English vocabulary learning application through short Qur'anic verses using a Computer-Based Instruction (CBI) approach. The application is designed to assist learners in improving their English vocabulary while simultaneously enhancing their understanding of selected Qur'anic verses. The learning materials are presented through various multimedia elements, including text, images, audio pronunciation, Qur'anic recitation, translations, explanations, quizzes, and progress-tracking features. The development process follows a systematic instructional design approach, integrating vocabulary learning with meaningful Qur'anic contexts to increase learner engagement and comprehension. The application consists of several main modules, namely Materials, Vocabulary, Qur'anic Verses, Quiz, Progress, and Achievements. These modules provide interactive learning experiences that encourage independent learning and continuous assessment. The resulting application offers an innovative learning environment that combines language acquisition, Islamic values, and educational technology. Through the implementation of multimedia and Computer-Based Instruction principles, the application is expected to improve learners’ vocabulary mastery, motivation, and overall learning outcomes. The study contributes to the development of technology-enhanced language learning media that integrates religious content with modern educational approaches.